The struggle between Ba’athist social nationalism and the communist discourse of the Iraqi Communist Party and its reflection on the Kurdish cause: From (February 8, 1963 – November 18, 1963) - Zhilwan Latif Yar Ahmad; Sozan Karim Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The Iraqi Communist Party, as a communist organization and representative of the Iraqi left and Marxists, opposed the Ba’athist Arab Socialist Party, which considered itself the agent of Arab nationalist thought, with a leftist discourse and propagandist of socialist thought. Both parties have become the most prominent political organizations that have had the greatest influence in the Iraqi political process for half a century, including the Kurdish national cause. This study attempts to present one of the most important of the different ideological discourses, which have had a direct impact on the organizational life and political maneuvers of both parties and a direct reflection on the Kurdish cause.